Determination of kinetic parameters during the pineapple peel drying process (Research, Society and Development, 2020)
The present work aims to perform a kinetics of pineapple peel drying at different temperatures and to adjust empirical and diffusive mathematical models for experimental data. The drying kinetics were performed at temperatures of 45, 55 and 65 °C, at a speed of 1.5 m/s. The experimental data were fitted with empirical (Newton Page and Parry) and diffusive mathematical models to consider an infinite wall geometry and a boundary condition of the third type. Among the mathematical models used or the page model that was the best adjusted to the experimental data of the pineapple peel drying kinetics, as it displays high values for the selection coefficient (R2), lower values for a chi-isolated function, in addition to random distribution for all applied temperatures. The values of diffusivity and convective coefficient have an influence on the increase in temperature, show direct proportionality and the minimum values of Biot number that are subjected to used start conditions (third type) displayed in a satisfactory way or process.